Downtown Safety, Security, and Development in New York City, 1984 - Milder, N. David ([Verlag nicht ermittelbar], 1990)
This data collection was designed to address problems of crime as a barrier to the economic health of three outlying commercial centers of New York City: Brooklyn, Fordham Road in the Bronx, and Jamaica Center in Queens. Included in the survey are variables concerning the respondent's age, race, gender, family income, length of residence, and personal victimization experience. Also included are variables pertaining to perceptions of safety, physical disorder in the area, and source of information about crime in the commercial center.